(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2007)
In late Paleocene-Eocene times, in the Tethyan area, the shallowest and most restricted carbonates deposited between the intertidal zone and the lower limit of the upper photic zones are characterized by Spirolina-dominated facies. This extremely shallow-water carbonate facies is recorded from the Cenomanian to the Miocene in the Tethyan realm with similar sedimentological characters and similar spiroliniform epiphytic taxa. All these taxa can be considered to reflect some kind of vicariance through time. In Southern Italy this peculiar facies is represented by the Trentinara Formation (Lower-Middle Eocene); in several stratigraphic sequences of this formation, three levels containing alveolinids were identified. The first is well known in the literature and allows us to assign the lowermost part of the Formation to the lowermost Ypresian (bio-chronozone SBZ 6, Alveolina ellipsoidalis zone); the second is not age diagnostic because alveolinids are rare and poorly preserved; the third allows the age of the upper part of the Trentinara Formation to be established as Early Lutetian (bio-chronozone SBZ 13, Alveolina stipes zone). The exact age of the top of the formation is still unclear, but probably falls within the Lutetian-Priabonian interval. The geographic locations of the most significant shallow-water carbonates of Early-Middle Eocene age, cropping out in the southern Apennines, have led to a first attempt to map their distribution within the central gyre of western Tethys.